MULTICULTURALISM AS A TROJAN HORSE OF BRITISHNESS : - Harutyunyan, Narine (Armenian Folia Anglistika, 2024)
This study is devoted to the multilayered and controversial problem of multiculturalism, in the context of national identity in the territory of modern Great Britain. The article deals with the problems of the transformation of the linguistic and cultural components of the life of the country, and the perception and acceptance of ethnic diversity by the population of Britain. Particular attention is paid to the emergence of new varieties of the English language - ethnolects and multiethnolects, resulting from the relationship between different ethnic groups in the context of multiculturalism. In the article, the author gives examples that testify to the fiasco of multiculturalism and reflects on the social and linguistic aspects of the process of integrating non-racial, non-religious migrants into European and, in particular, English society. The paper considers such a phenomenon as the “cancellation culture” of the white race. The questions of the formation of a hybrid identity are touched upon, as well as concerns are expressed about the possible negative impact of the osternization of Europe.